The Technological Innovations and Their Impact on the Economy - Maslennikov, Mikhail Ivanovich (Economy of Regions, 2017)
Drastic and inclusive technology progress is changing the economy of Russia and foreign countries. This progress significantly impacts production forces.. This paper analyzes theoretical and applied approaches to the investigation of production forces development. I reveal the role and importance of innovations in science and technology as well as their impact on various segments of the economy. I analyze the conceptual framework used for technological shifts. The paper describes the indicators showing the level of scientific and technological potential development in various countries and regions including the Urals. I define growth areas in technology and assess their contribution to gross domestic product (GDP) growth. The administrations and authorities at federal and regional levels impact the development of science, innovations, technologies and breakthrough areas. The development of these spheres leads to the increase in productivity of social activities, production and business activity. The paper reveals the impact of the technological breakthrough in such latest fields as the alternative energy sources, drones, electric car industry, storage and delivery of energy. This fields transform the economy and society. Furthermore, they change theoretical concepts of functional and institutional social structure. The development paradigm is to be modified from fuel and raw model to the innovative and technological one. The economic development and scientific and technological potential are interrelated. I discuss the reason of close attention to the development of science, technologies, innovations in the developed countries. as well as the measures to stimulate their development. The article studies the mechanism and tools of science and education funding in various regions of the world. The results of the research may be used for updating the strategy of scientific and technological development of Russia and its regions in the current situation as well as for choosing necessary conceptual approaches to the development of the economy.